2004
DOI: 10.1159/000078353
|View full text |Cite
|
Sign up to set email alerts
|

Do White Matter Changes Have Clinical Significance in Alzheimer’s Disease?

Abstract: Background: Although white matter changes visible with MRI are generally considered to result from ischemia, it has become clear that these changes also appear in patients with Alzheimer’s disease (AD). However, their significance in AD is unknown. Objective: We evaluated the clinical significance of white matter changes in AD. Methods: Ninety-six AD patients (79.4 ± 5.92 years old) and 48 age-matched control subjects (80.0 ± 7.03 years old) participated in the study. Three neuroradiologists assessed the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
12
1
1
Order By: Relevance
“…In line with previous theories [18][19][20][21][22] , the present study confirmed that the cognitive function of AD patients at baseline was mostly unaffected by MR lesions, including those on the cholinergic pathways, or hippocampal size. Among them, WMH showed a tendency to be associated with lower CDT scores ( ␤ = -0.52, p = 0.06).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous theories [18][19][20][21][22] , the present study confirmed that the cognitive function of AD patients at baseline was mostly unaffected by MR lesions, including those on the cholinergic pathways, or hippocampal size. Among them, WMH showed a tendency to be associated with lower CDT scores ( ␤ = -0.52, p = 0.06).…”
Section: Discussionsupporting
confidence: 92%
“…White matter hyperintensities (WMH) are associated with slow psychomotor speed [10][11][12] , depression [13][14][15] and sometimes memory impairment [16,17] , but not with the severity of AD [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…These negative results could be due to poor investigation of cognitive skills specifically subserved by frontal-subcortical circuits [15,16] and to the methodology adopted in rating WMC that disregards the role of cortical atrophy [49] as well as the location of WMC lesions [15,35] . A study paying attention to just lobar distribution of white matter lesions displayed a relationship between frontal WMC volumes and Category Fluency in a small sample of AD cases [17] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, AD has been proposed as a clinical syndrome with two radiological expressions, with and without small vessel disease [14] . However, data on the frequency [2] and clinical relevance of WMCs in AD are still controversial and lack evidence of a specifi c effect of WMCs on global measures of mental impairment [15] , even when the location of the lesions has been considered [16] . A survey focused on WMCs in healthy aging and vascular dementia/AD patients detected a relationship between frontal WMC volumes and verbal category fl uency just in a small subgroup of AD cases [17] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although neuroimaging and pathoanatomic studies have confirmed both macroscopic and microscopic white matter changes in patients with AD and MCI, controversy exists regarding the clinical relevance of these changes and the mechanisms underlying them. [4][5][6][7] By taking advantage of the anisotropic nature of water diffusion in biologic tissues, the diffusion tensor imaging (DTI) technique provides increased sensitivity for detecting ultrastructural abnormalities of white matter in vivo. 8 This is true even in regions that appear normal on traditional MR imaging sequences (so called normal-appearing white matter [NAWM]).…”
mentioning
confidence: 99%